A commentary on Book 4 of Valerius Flaccus' Argonautica - Murgatroyd, Paul. (Mnemosyne, Supplements, 2009)
This volume consists of an introduction, the text of book 4 of Valerius Flaccus' Argonautica , commentary, bibliography and index. However, it is not a standard philological commentary. Although it contains textual criticism (but only where meaning and appreciation are substantially affected) and explanation of sense and references (a vital basis for critical analysis), above all there is literary appreciation of Valerius' fourth book, which should help to bring about a revaluation of this largely neglected and sadly underestimated author. The book alerts readers to important aspects of Valerius' highly intellectual poetry, such as wit, humor, elegance, point, subtlety, narrative skill, and creative engagement with forerunners, especially Apollonius of Rhodes and Virgil.